Coping strategies minimize the tendency of post-power syndrome to civil servants before retirement - Hamidah, Firdausy Asmi Ramadhani, (Opción, 1970)
The aim of this research is to discover the correlation between coping strategies (emotion focused coping and problem focused coping) and the tendency of post-power syndrome experienced by civil servants before retirement. The respondents of this research were 41 civil servants before 1 to 2 years retirement. The data was collected by using questionnaire. The result showed that there was a significant negative correlation between coping strategies and the tendency of post-power syndrome, with a correlation coefficient of -0,471 and a significant value of 0,002 towards problem focused coping; and emotion focused coping showed a correlation coefficient of -0,335.